2010
DOI: 10.1073/pnas.1000935107
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxis signaling protein CheY binds to the rotor protein FliN to control the direction of flagellar rotation in Escherichia coli

Abstract: The direction of rotation of the Escherichia coli flagellum is controlled by an assembly called the switch complex formed from multiple subunits of the proteins FliG, FliM, and FliN. Structurally, the switch complex corresponds to a drum-shaped feature at the bottom of the basal body, termed the C-ring. Stimulus-regulated reversals in flagellar motor rotation are the basis for directed movement such as chemotaxis. In E. coli, the motors turn counterclockwise (CCW) in their default state, allowing the several f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
194
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(195 citation statements)
references
References 42 publications
1
194
0
Order By: Relevance
“…An independent two-sample t test indicated that this difference was significant (P < 0.001). We did not observe significant correlation between FliM numbers and rotational velocities over a range of speeds typical for tethered cells (1)(2)(3)(4)(5)(6)(7)(8).Because the results of the cryo-EM studies might have been biased, we consider the ratio of the average number of FliM subunits in a given motor to that observed for motors in the CW …”
mentioning
confidence: 94%
“…An independent two-sample t test indicated that this difference was significant (P < 0.001). We did not observe significant correlation between FliM numbers and rotational velocities over a range of speeds typical for tethered cells (1)(2)(3)(4)(5)(6)(7)(8).Because the results of the cryo-EM studies might have been biased, we consider the ratio of the average number of FliM subunits in a given motor to that observed for motors in the CW …”
mentioning
confidence: 94%
“…The switching probability is modified by a chemotactic signal transduction pathway (1,6). The binding of a chemotactic signalling protein, phospho-CheY (CheY-P), to FliM and FliN is thought to induce a cooperative conformational change in the C-terminal FliG domains of the C ring, resulting in a different rotor-stator interaction to allow the motor to spin in the CW direction (16,17). The switching probability increases linearly with increase in motor torque in both directions, suggesting that the switch senses the load on the stator-rotor interaction as well as the level of CheY-P (18).…”
mentioning
confidence: 99%
“…Non-phosphorylated CheY interacts weakly with the FliM switch proteins of the flagellar motor, which are the final effectors of the sensory transduction chain [42][43][44][45]. Because of the only weak interaction between unphosphorylated CheY and FliM, CheY is not able to break up the FliNFliN interaction within the FliN-dimer via the N-terminal hydrophobic patch [46]. Thus, a CheY-FliN interaction does not take place and a counterclockwise rotation of the flagella is induced leading to a fast straightforward movement of the bacterial cell, a so-called "run".…”
Section: Experimental Approachesmentioning
confidence: 99%
“…CheY-P interacts as well with the N-terminal parts of the FliM proteins of the motor switch complex but in a stronger way than non-phosphorylated CheY [43]. This stronger binding tethers CheY-P to FliM so that it is able to break up FliN-dimers to bind to FliN [46]. Thus, it triggers a clockwise flagellar rotation resulting in bacterial "tumbling" [44,46].…”
Section: Experimental Approachesmentioning
confidence: 99%
See 1 more Smart Citation